Air-Sea Gas Fluxes and Remineralization From a Novel Combination of pH and O2 Sensors on a Glider - Possenti, Luca; Humphreys, Matthew P.; Bakker, Dorothee C. E.; Cobas-García, Marcos; Fernand, Liam; Lee, Gareth A.; Pallottino, Francesco; Loucaides, Socratis; Mowlem, Matt Charles; Kaiser, Jan (Frontiers in Marine Science, 2021)
Accurate, low-power sensors are needed to characterise biogeochemical variability on un-derwater glider missions. However, the needs for accuracy and low power consumption can be difficult to reconcile. To overcome this difficulty, we integrated a novel sensor combina-tion into a Seaglider, comprising a spectrophotometric lab-on-a-chip (LoC) pH sensor and a potentiometric pH sensor, in addition to the standard oxygen (O2) optode. The stable, but less frequent (every 10 min) LoC data were used to calibrate the high-resolution (1 s) poten-tiometric sensor measurements. The glider was deployed for a 10-day pilot mission in Au-gust 2019. This represented the first such deployment of either type of pH sensor on a glider. The LoC pH had a mean offset of +0.005±0.008 with respect to pH calculated from total dis-solved inorganic carbon content, c(DIC), and total alkalinity, AT, in co-located water sam-ples. The potentiometric sensor required a thermal-lag correction to resolve the pH varia-tions in the steep thermocline between surface and bottom mixed layers, in addition to scale calibration. Using the glider pH data and a regional parameterisation of AT as a function of salinity, we derived the dissolved CO2 content and glider c(DIC). Glider surface CO2 and O2 contents were used to derive air-sea fluxes, Φ(CO2) and Φ(O2). Φ(CO2) was mostly directed into the ocean with a median of –0.4 mmol m–2 d–1. In contrast, Φ(O2) was always out of the ocean with a median of +40 mmol m–2 d–1. Bottom water apparent oxygen utilisation (AOU) was (35±1) µmol kg–1, whereas apparent carbon production (ACP) was (11±1) µmol kg-1, with mostly insignificant differences along the deployment transect. This deployment shows the potential of using pH sensors on autonomous observing plat-forms such as Seagliders to quantify the interactions between biogeochemical processes and the marine carbonate system at high spatiotemporal resolution.